Input and Output Matched SiGe RF Mixer with High Dynamic Range - Cam, Zehra Gulru; Palamutcuogullari, Osman (IEEE, 2013)
An active mixer operating at 2.15 GHz which is based on the Gilbert Mixer topology is designed by using the transistors which are realized by using 0.25um SiGe technology. The symetrical driving circuit at the input is realized by using the CB(common base) and CE(common emitter) transistors which operate interactively. The passive capacitive voltage-series feed-forward circuit is applied to CB circuit and an almost perfect broadband matching is obtained at the input. Mixer is simulated with AWR software environment. 5V DC supply voltage is used, OIP3 of 24.7 dBm and the Conversion Gain of 3 dB is obtained for the -2.5 dBm of LO power. The noise figure of the circuit is simulated as 11.75 dB.
Keywords: Engineering